Implementation of Islamic Communication Principles in High School Counseling Guidance in East Kalimantan - Ida Suryani Wijaya; Muhammad Tahir; Rega Armella; Andi Muhammad Abdi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of carrying out this research is to find out how the implementation of the principles of Islamic communication in the implementation of guidance and counseling and the supporting factors and inhibiting factors. This study uses a type of qualitative research with field research research methods (Field Research). The data source for this research is the subject where the data is obtained, namely the respondent. The main data sources come from interviews and observations of high school guidance and counseling teachers in East Kalimantan. Data collection techniques used are interviews, observation and documentation. The results of the research will be analyzed using a qualitative descriptive method. The results showed that the implementation of the principles of Islamic communication in Guidance and Counseling for Senior High Schools in East Kalimantan was running effectively which was proven by the delivery of guidance and counseling messages which contained the principles of counseling guidance, including: good and true words (Qaulan Sadidan and Qaulan Ma'rufa), communicative words (Qaulan Balighan), light words (Qaulan Masyura'), gentle words (Qaulan Layyina), and noble words (Qaulan Karima). The supporting factors in the implementation of counseling guidance are adequate and competent human resources, visible and invisible facilities and infrastructure, forms of cooperation between parents and the school, as well as periodic supervision. The inhibiting factors of the implementation of counseling guidance are the knowledge gap and the background of the students.